The Implementation of Extensive Reading and the Contribution to Students’ Independent Learning. - indy putra darana hariyanto (Language-Edu, 2020)
This research concerns with the implementation of extensive reading and the contribution to students’ independent learning. In addition, the purposes of this research are to explore the implementation of extensive reading at SMP in Malang and to inspect the contribution of extensive reading to the development of the students’ independent learning at SMP in Malang. This research used descriptive qualitative design. This research aimed to define the contribution of extensive reading to the development of the students’ independent learning at SMP in Malang. Moreover, the instruments that used in this research were questionnaire and interview. Based on the result of data analysis, the researcher can conclude that all respondents implemented the extensive reading. In addition, the application of extensive reading at SMP in Malang should adjust the school situation because it should adjust the available time. There was not much time available to implement a well-scheduled extensive reading. In addition, the teacher tried to overcome this problem by providing time to implement extensive reading both using part of the class allocation time and at the inactive hour in class. Furthermore, there were nine categories of the questions developed into twenty-eight statements in the form of close-ended questionnaire to examine the contribution of extensive reading to the development of the students’ independent learning. All in all, from all statements could be concluded that the majority of the students agreed with the statements contained in the questionnaires. It can be concluded that, extensive reading has a contribution on students' independence learning at SMP in Malang.Keywords: Extensive reading, Independent learning